A consequence of a tragedy: nowcasting poverty rate in Syria. (1st October 2020) - Hamati, Samer
Abstract : It seems that the current conflict in Syria is finishing, and a new phase of rebuilding is starting sooner. Setting a rebuilding strategy requires finding detailed and up-to-date figures, a challenging task to do in a time of conflict. We take the venture and compute poverty figures and profile during the conflict using nowcasting techniques based on a sample of households covered in the household income and expenditure survey (HIES) 2009. In addition to the practical importance of this article regarding the rebuilding process strategy of Syria, the article makes a methodological contribution to nowcast the poverty rates in countries plagued with civil conflicts.